Does shareholder activism have a long-lasting impact on company value? A meta-analysis - Josef Bajzík (Charles University in Prague, Institute of Economic Studies (IES), 2024)
I collect 1,186 reported estimates of long-run value creation from 49 studies and present the first meta-analysis of the literature on shareholder activism and its effect on firm value in the longrun. This synthesis is necessary because shareholder activism is increasing over time and across countries. The study shows that the conclusion as to whether activism is beneficial depends on the benchmark with which the targeted firm is compared. Second, the estimates are also overstated due to publication bias. Third, the value added by activism depends on the country-specific regulátory framework.
Keywords: G14; G30; G34; L20; 330; Abnormal return; event study; long run; meta-analysis; model averaging; publication bias; shareholder activism